Detection of spleen abscesses facilitates diagnosis of melioidosis in Malaysian children - Mohan, Anand; Manan, Kamilah; Tan, Lee See; Tan, Yee Chin; Chin, Shi Tying; Ahmad, Rohani; Hamli, Qairul Irwan; Chuah, Teik-Beng; Chien, Su Lin; Teck Lau, Peter Sie; Podin, Yuwana; Ooi, Mong How (Elsevier, 2020)
Objectives Melioidosis is associated with extremely high case fatality ratios. The aim of this study was to determine whether detection of abdominal visceral abscesses can facilitate diagnosis of melioidosis in children.